Technological Diversification In The Promotion And Counter-Propaganda Of Spiritual And Educational Work - Pardayev Sobit Abduvali oglu. (Zien Journals, 2022)
Explains the technological approach to the implementation of propaganda and counterpropaganda work among young people and the extent to which it has a positive impact on the minds of young people and the essence of the ongoing process of renewal in Uzbekistan; formation of devotion to our national customs and traditions; formation of social skills and competencies for high spirituality and enlightenment; teaching creativity, free and independent thinking; respect for the elderly, respect for the young, and the promotion of a culture of community control in the neighborhood
Keywords: spirituality-enlightenment; propaganda; technology; ideology